ANALISIS USAHA PEMBIBITAN MATOA PADA CV KEBUN SARI DI KOTA BENGKULU (Business Analysis of Matoa Seedling Production at CV Kebun Sari in Bengkulu City) - BONITA, YESHA; KURNIATI, NOVITRI; EFRITA, EDI; MUTMAINNAH, ELNI (Universitas Mulawarman (University of Mulawarman), 2026)
The matoa nursery business has strong potential in tropical fruit agribusiness development; however, its sustainability depends on cost efficiency and financial viability. This study aimed to determine whether this business is financially feasible and economically viable. The method applied is a case study approach with descriptive quantitative analysis, using data on production costs, revenue, and profit per production cycle. The results showed a total production cost of IDR 75,016,083.33 with revenue of IDR 240,000,000, resulting in a profit of IDR 164,983,916.67 per production period. The R/C ratio was 3.20 and the B/C ratio was 2.20, indicating high cost efficiency and profitability. The break-even point for production is 3,750.80 seedlings and IDR 75,016,083.33 in sales. This is far below the realization of sales of 12,000 seedlings or IDR 240 million, indicating a large safety margin. Thus, the matoa nursery business at CV Kebun Sari is declared feasible and has the potential to be developed comprehensively.